Utilization of Rice Husk and Tea Waste as Charcoal Briquettes with Molasses Adhesive - Ahmad Rifai Siregar; Lukman Adlin Harahap; Sulastri Panggabean (Universitas Sumatera Utara, 2015)
Briquette is one of the biomass fuel. Briquette is used as an alternative energy sources which is very simple and inexpensive. Biomass used in this research were rice husk and tea waste. The aim of this research was to find composition of Bio-Carbon Briquette processing of rice husk and tea waste and to determine the best Bio one. Testing was conducted using a non-factorial completely randomized design with parameters of water content, density, firmness press, calorific value, and ash content. The results of this research showed that the composition of the briquette materials was unaffected the water content and had highly significant effect on density, firmness press, calorific value, and ash content. The best water content in this research was 5.80%, that met Japanese, America, England and Indonesia standards. The Density value was 0.75 g / cm3 which dit not met briquettes of Japanese, America, England and Indonesia standards. The best of fumness press in this research was 2.37kg/cm2did not met the standards of briquette of Japanese, America, England and Indonesia. The best of calofic value in this research was 5661.41 kal/gr that met the standards of briquette of Indonesia, but did not met standards of briquette of Japanese, England, and America. The best of ash content valuein the research was 5.876% that met the standards of briquette of Indonesia, Japanese, England and America. Keywords : briquette, biomass, rice husk and tea waste.